Formulation And Anti-Aging Effectiveness of Sheet Mask Formula Containing Macadamia Oil - Adrianie Maricella; Ermi Girsang; Ali Napiah Nasution; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
Aging is an inevitable physiological process that must be experienced by every human being. This process is irreversible which includes all organs of the body including the skin. The skin is one of the tissues that will directly show the aging processes. Premature aging can happen to anyone. Especially in Indonesia, which is a tropical climate country with higher intensity sunlight. The degenerative process in skin that is too often exposed to ultraviolet light takes place more quickly to aging. Premature aging can happen to anyone. Especially in Indonesia, which is a tropical climate with higher intensity sunlight. The degenerative process in skin that is too often exposed to ultraviolet light takes place more quickl.